2002
DOI: 10.2519/jospt.2002.32.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Muscular, Skeletal, and Neural Adaptations Following Spinal Cord Injury

Abstract: Spinal cord injury is associated with adaptations to the muscular, skeletal, and spinal systems. Experimental data are lacking regarding the extent to which rehabilitative methods may influence these adaptations. An understanding of the plasticity of the muscular, skeletal, and spinal systems after paralysis may be important as new rehabilitative technologies emerge in the 21st century. Moreover, individuals injured today may become poor candidates for future scientific advancements (cure) if their neuromuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 39 publications
(87 reference statements)
2
110
2
3
Order By: Relevance
“…For the hip, distal femur, and proximal tibia, BMD was lower in people with SCI, a finding that generally agrees with different measurement methods from previous reports. 3,11,12,24 No difference existed between the BMD of the 2 groups at the lumbar spine. One explanation for this dissociation between the lumbar spine and the hip is that during wheelchair use after SCI, the lower extremities receive very little loading.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For the hip, distal femur, and proximal tibia, BMD was lower in people with SCI, a finding that generally agrees with different measurement methods from previous reports. 3,11,12,24 No difference existed between the BMD of the 2 groups at the lumbar spine. One explanation for this dissociation between the lumbar spine and the hip is that during wheelchair use after SCI, the lower extremities receive very little loading.…”
mentioning
confidence: 89%
“…Bone mineral density (BMD) of the paralyzed extremities declines precipitously in the first 2 years after SCI, eventually reaching a level below fracture threshold. [1][2][3][4] Between 1% and 6% of people with SCI will sustain fractures in their paralyzed extremities. [5][6][7] Fractures are often caused by trivial insults to the limbs 5,7,8 that people with SCI frequently encounter during everyday mobility.…”
mentioning
confidence: 99%
“…Previous investigators reported on electrophysiological changes that occur to peripheral and central structures following primary spinal insult [73][74][75][76][77][78][79][80][81]. While electrophysiological testing has been performed in SCI for predicting injury [74][75][82][83][84][85], examining the nature of neurological injury [71][72][86][87][88][89][90][91][92], monitoring the integrity of spinal conduction [77,[93][94], and assessing for concomitant or secondary neurological conditions [95][96][97][98][99], its role as a method of evaluating the impact of various interventions [65][66][81][82][100][101][102][103][104][105][106] is the concern of this article.…”
Section: Electrodiagnosticsmentioning
confidence: 99%
“…2,3 Improvements in functional ability, however, vary greatly and the incidence of disability remains high. 4,5 Previous data suggest that persons after incomplete SCI produce less voluntary torque about the knee and ankle than non injured controls. Perhaps more importantly, impairments in the ability to produce torque in a timely manner as well as a reduced walking velocity are also common to these persons.…”
Section: Introductionmentioning
confidence: 99%